An analysis of fiscal decentralization as a strategy for improving revenue performance in Ugandan Local governments - Balunywa, Waswa; Nangoli, Sudi; Mugerwa, George W.; Teko, Juma; Mayoka, Kituyi G. (Journal of Research in International Business and Management, 2014)
The inception of decentralization in late the 1990s in Uganda instilled so much hope in the people of Uganda as they anticipated that local governments would improve on revenue collection and service delivery. This was to be achieved through a privatization strategy which guaranteed better performance in revenue collection as compared to the previous system where government employees embezzled most of the taxes they collected. To date however, a number a number of challenges have made it hard fiscal decentralization to realize any fruits. This study was conducted to examine the impact of fiscal decentralization on revenue performance in Ugandan local governments. A cross-sectional survey research design involving both quantitative qualitative research methods were used in the study. A questionnaire was employed to collect and analyze quantitative data, while an interview guide was used to collect qualitative data. The study population included LC III, LC IV and LC V council members and technical members of staff in three local government districts of Mbale, Manafwa and Kampala. Both random and purposive sampling techniques were used to select a total sample of 600 respondents. Results indicate that fiscal decentralization helps to reduce corruption, leads to improved revenue performance, enables better planning for revenue collection, reduces on tax evasion, enables the local unit to get more sources of revenue, makes it easy to handle taxation disputes and also that Fiscal decentralization reduces on taxation bureaucracies hence better revenue performance. This paper posits that for improved revenue performance in a decentralized government, there is need to restrict political leaders from interfering with the work of technical staff, institution of tougher penalties for tax evaders, and also that there was need for central governments to increase funding to the local units. The findings also indicate that salaries for technical staff should be increased to minimize corruption and improve on revenue performance.
Keywords: Fiscal Decentralization; Revenue Performance; Local Government; Uganda